Training as Part of Capacity Building : Recent Initiatives and Strategic Considerations. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2008)
This paper focuses on the IMF's training program as part of the Medium-Term Strategy (MTS) for capacity building in member countries.1 It updates Executive Directors on the current features of the program, reviews the efforts that have been made in recent years to strengthen the curriculum and to enhance value for money, and considers options for boosting external financing of training through charging and increased donor contributions. The paper also provides background for addressing the following issues: - Are the objectives of IMF training fully consistent with the broader objectives of the institution? And are these training objectives being met? - Is Fund training efficiently organized-i.e., is the current degree of decentralization sensible? - Are adequate evaluation and feedback mechanisms in place? -In the absence of market signals and with a large unsatisfied demand, how can we determine the 'right' volume of training and how can we assess its worth?
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Comparator Training Organization; IMF Training; Participant Cost; PP; Training Department; China, People's Republic of